Sistema de gestión deportiva integral para natación Castaño - Macías Bermeo, Luis Antonio (2025)
This study addressed the implementation of a comprehensive sports management system for the Natación Castaño club in Chone, aiming to optimize the administration of its records and activities. The Extreme Programming (XP) methodology was employed, structured into planning, design, coding, and testing phases to ensure software adaptability. Functional and non-functional requirements were identified through interviews with key club stakeholders, allowing the definition of features such as user registration, payment management, and athlete performance tracking. The design was based on the Model-View-Controller architectural pattern, using Unified Modeling Language (UML) and a MySQL database for efficient management. Development was carried out with technologies including Angular for the frontend and PHP with Laravel for the backend. Finally, unit, integration, visualization, and performance testing were conducted to ensure proper system functionality and usability, resulting in the deployment of a digital tool that replaces manual processes and facilitates decision-making.